Does a whole body vibration intervention have any effect on adiposity in elderly people? - Alba Gómez-Cabello; Alejandro González-Agüero; Ignacio Ara Royo; José Antonio Casajús Mallén; Germán Vicente-Rodríguez (Asociación Española de Ciencias del Deporte, 2016)
Introduction: The ageing process is accompanied by an increase in fat mass (FM) and a redistribution of the adipose tissue, which are associated with several pathologies. The aim of this study was to test if an 11-weeks whole body vibration (WBV) intervention has any effect on FM in older adults. Material and Methods: Forty-nine non-institutionalized seniors (20 men) participated in the study. Twenty-four participants (75.2±4.7 years) trained static squat-positioned on a WBV platform three times per week for eleven weeks. The remaining 25 (74.8±4.9 years) were allocated into the control group (CON). FM at the whole body, trunk, upper and lower limbs was assessed via DXA. Results: WBV and CON groups showed similar values for FM at every body region during pre- and post-testing. No significant within group variations were detected at total, trunk or arms FM; however, there was a significant decrease in legs FM in both groups (p<0.05). Discussion: From the obtained results, it can be concluded that an 11-weeks WBV therapy is not an effective method for reducing fat mass in older adults. Therefore, the use of the WBV devices available on the market, aiming weight loss or FM decreases should be avoided in this population.